Safety of Combination of a Tetravalent Meningococcal Conjugate Vaccine Against Serogroups A, C, Y, W-135 With Other Vaccine Preparations: a Prospective Study of a Series of Cases Among Healthy Children and Children With Various Health Abnormalities - Leyla S. Namazova-Baranova; Daria A. Novikova; Marina V. Fedoseenko; Anna G. Gaivoronskaya; Natalia E. Tkachenko; Tatiana A. Kaljuzhnaya; Firuza Ch. Shakhtakhtinskaya; Marika I. Broeva ("Paediatrician" Publishers LLC, 2017)
Meningococcal infection is an acute disease caused by Neisseria meningitidis, which proceeds with a diverse clinical aspect from nasopharyngitis to meningococcal meningitis and meningococcemia. Since 2014, a tetravalent meningococcal conjugate vaccine has been registered in Russia. This vaccine creates protection against serogroups A, C, W-135, Y and can be used from the age of nine months to 55 years. The actual issue is a vaccine tolerability, including when combined with other vaccine preparations.Objective: Our aim was to evaluate the safety of a tetravalent meningococcal conjugate vaccine against serogroups A, C, Y and W-135 when it is combined with other vaccine preparations.Methods. A prospective full-design study assessed the tolerability of immunization with a meningococcal conjugate vaccine, both in case of monovaccination and in combination with a pneumococcal 13-valent conjugate vaccine, measles-mumps-rubella, viral hepatitis A, influenza, and chicken pox vaccines.Results. 97 children aged from 9 months to 18 years were vaccinated, 20 of them were healthy and 77 had medical issues (with allergic pathology, ENT diseases, cardiovascular and nervous system diseases, lung diseases as well as orphan diseases). Among vaccinated children, general reactions were observed in 3/97 (3.1%) children, local reactions - in 5 (5.2%). The post-vaccination period passed asymptomatically and uneventfully in the prevailing majority of children vaccinated with a tetravalent meningococcal conjugate vaccine (in 91, 93.8%).Conclusion. The immunization with a tetravalent meningococcal conjugate vaccine against serogroups A, C, Y, W-135 is well tolerated, both in case of monovaccination and in combination with other vaccine preparations, in healthy children of different age groups and in patients with different health status.